Statins in hypercholesterolaemia: a dose-specific meta-analysis of lipid changes in randomised, double blind trials - Edwards, J; Moore, R (BioMed Central, 2003)
Background: Statins alter lipid concentrations. This systematic review determined the efficacy of particular statins, in terms of their ability to alter cholesterol. Review methods: PubMed, the Cochrane Library, references lists of reports, and reviews were searched (September 2001) for randomised, double blind trials of statins for cholesterol in trials of 12 weeks or longer. Mean change in total cholesterol, LDL-cholesterol, HDL-cholesterol, and triglycerides was calculated using pooled data for particular statins, and for particular doses of a statin. Pre-planned sensitivity analyses were used to determine the effects of initial concentration of total cholesterol, study duration, the effects of major trials, and effects in placebo versus active controlled trials. Information was not collected on adverse events. Results: Different statins at a range of doses reduced total cholesterol by 17–35% and LDLcholesterol by 24–49% from baseline. Lower doses of statins generally produced less cholesterol lowering, though for most statins in trials of 12 weeks or longer there was at best only a weak relationship between dose and cholesterol reduction. Duration of treatment and baseline total cholesterol concentration did not alter the amount of the benefit attained. Conclusions: Statins are effective medicines and confer benefit to patients in terms of primary and secondary prevention of coronary heart disease. Reductions in total cholesterol of 25% or more and LDL cholesterol of more than 30% were recorded for fixed doses of simvastatin 40 mg, atorvastatin 10 mg, and rosuvastatin 5 mg and 10 mg.